Strategi Pengembangan Obyek Wisata Di Wilayah Makam Bung Karno Kota Blitar - Agus Zainal Arifin (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This research is a type of descriptive research with qualitative research methods. So that this method can describe and analyze the swot strategy for increasing the competitiveness of the development of regional tourism in the City of Blitar (Settlement of Tourism Supporters as an Effort to Increase Competitiveness in the Development of Tourism Objects of Bung Karno's Tomb of Blitar City) The implementation of this method is not limited to data collection and preparation , but also includes analysis and interpretation of the data. Data analysis techniques used are descriptive analysis techniques with data reduction steps, and conclusion drawing. The results showed that the Research on Housing and Settlement Area Development Plans in the Jatimalang Embankment and Bendung Tanggung Areas was the development of tourism-based housing and settlements. In the sense that there has been a mutually beneficial collaboration including, both residential and residential areas and tourism areas, in this case the concept of the need to establish regional management institutions for Tourism Settlement Settlement as an Effort to Increase Competitiveness in the Development of Tourism Objects of the Bung Karno Tomb of Blitar City which is a joint representation for all residents of Kepanjenkidul Subdistrict, especially the Sentul Village and the City of Blitar.